2020
DOI: 10.33988/auvfd.623821
|View full text |Cite
|
Sign up to set email alerts
|

The effects of fumaric and malic acids on the in vitro true digestibility of some alternative feedstuffs for ruminants

Abstract: The aim of this study was to determine the effects of the addition of different amounts of fumaric acid (FA) and malic acid (MA) to the leaves of Robinia pseudoacacia (Black locust, acacia), Prunus laurocerasus (cherry laurel), Quercus cerris (oak), and Camellia sinensis (tea factory wastes, TFW), to improve their value as alternative feeds for ruminants. The parameters examined were the in vitro true digestibility of feed (IVTDAs fed), dry matter (IVTDDM), organic matter (IVTDOM), neutral detergent fiber (IVT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Replacement of berseem hay with malic or lactic acid-treated DPL did not affect DM or NDF degradability. Similar results were observed by El-Zaiat et al [8] and Genc et al [34] who observed unaffected Table 3 In vitro ruminal total gas and methane (CH 4 ) and carbon dioxide (CO 2 ) production kinetics of rations containing different levels of date palm leaves ensiled without additives, with lactic acid or malic acid treated 1 Date palm leaves at different forms (ensiled without additives, with lactic acid or malic acid) replaced berseem hay at 0, 25, 50, 75, or 100%, DM basis 2 b is the asymptotic total gas or CH 4 or CO 2 production (mL/g DM); c is the rate of total gas or CH 4 or CO 2 production (/h); Lag is the initial delay before total gas or CH 4 or CO 2 production starts (h) SEM standard error of the mean Ration 1 Replacement level Total gas production (mL/g DM) 2 CH 4 production (mL/g DM) 2 CO 2 production (mL/g DM) nutrient degradability with malic acid in vitro administration. In another experiment, Ebrahimi et al [35] and Pal et al [36] observed that fumaric or malic acids did not affect the digestibility of DM, OM, NDF, and ADF.…”
Section: Degradability and Fermentationsupporting
confidence: 90%
“…Replacement of berseem hay with malic or lactic acid-treated DPL did not affect DM or NDF degradability. Similar results were observed by El-Zaiat et al [8] and Genc et al [34] who observed unaffected Table 3 In vitro ruminal total gas and methane (CH 4 ) and carbon dioxide (CO 2 ) production kinetics of rations containing different levels of date palm leaves ensiled without additives, with lactic acid or malic acid treated 1 Date palm leaves at different forms (ensiled without additives, with lactic acid or malic acid) replaced berseem hay at 0, 25, 50, 75, or 100%, DM basis 2 b is the asymptotic total gas or CH 4 or CO 2 production (mL/g DM); c is the rate of total gas or CH 4 or CO 2 production (/h); Lag is the initial delay before total gas or CH 4 or CO 2 production starts (h) SEM standard error of the mean Ration 1 Replacement level Total gas production (mL/g DM) 2 CH 4 production (mL/g DM) 2 CO 2 production (mL/g DM) nutrient degradability with malic acid in vitro administration. In another experiment, Ebrahimi et al [35] and Pal et al [36] observed that fumaric or malic acids did not affect the digestibility of DM, OM, NDF, and ADF.…”
Section: Degradability and Fermentationsupporting
confidence: 90%
“…In their study comparing the techniques of estimating the digestibility of feeds, Damiran et al (2008) reported that the DM and NDF digestion values found in Daisy ıı method were higher than those found in vitro and in situ methods. Genç et al (2020) examined the effect of the addition of fumaric and malic acids to some alternative feeds on their in vitro true digestibility for ruminants and reported that the TDMD values were within the range of 45.47-60.66%, the TNDFD values were within the range of 11.17-17.46%, and the TOMD values were within the range of 45.40-60.63%.…”
Section: In Vitro Digestibility and Rfq Values Of The Feedsmentioning
confidence: 99%
“…Fumaric acid at 2% of the diet of sheep increased the activities of xylanases and amylase in the rumen [ 27 ]. Ebrahimi et al [ 28 ] and Genç et al [ 29 ] observed that malic acid administration decreased protozoal numbers in a dose-dependent manner. Decreasing protozoa increases ruminal bacteria because protozoa are the main predator of ruminal bacteria [ 30 ], which may explain the observed digestibilities.…”
Section: Discussionmentioning
confidence: 99%
“…Lactic acid treatment increased DM digestibility compared with malic acid, which may be related to the long-chain organic acids [ 31 ]. Genç et al [ 29 ] stated that the effect of organic acids on ruminal bacteria depends on their chemical composition. Gram-positive bacteria are more sensitive to long-chain acids, while Gram-negative bacteria are more sensitive to acids with less than eight carbon atoms.…”
Section: Discussionmentioning
confidence: 99%